Selected elements of the human resources management on the example of the Forge Plant “Glinik” - Oruba Aleksandra (My University, 2006)
Human Resources Management includes a broad range of phenomenon from economics, marketing, finance, law as well as psychology fields. The basic aim of this thesis is an attempt to analyze on the basis of available literature and empirical materials, processes related to human resources management in the Forge Plant “Glinik”. The author analyzed the theoretical aspects of HRM, including the essence and concept of human resources management, functions of the human resources management, employment of the workers, training process, as well as the essence and the meaning of the employees’ motivation. Historical background and the production process and organizational structure of the company are introduced. The recruitment, training and motivation processes in the Forge Plant “Glinik” are evaluated.
Wybrane elementy zarządzania zasobami ludzkimi na przykładzie Kuźni "GLINIK" w Gorlicach
Keywords: human resources management; functions of HRM; training; motivation; recruitment; employment